Comparative post-hatching ontogeny of Pseudoplatystoma reticulatum (Eigenmann & Eigenmann 1889) and Leiarius marmoratus (Gill, 1870) and their hybrid - Coelho, Geovanna Carla Zacheo [UNESP]; da Silva Costa, Raphael [UNESP]; Porto-Foresti, Fábio [UNESP]; Verissimo-Silveira, Rosicleire [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (Hindawi, 2021)
Ontogenetic studies of the eggs and larvae of fish can provide information on the initial life history and biology of a species, are important for taxonomic and evolutionary studies, and for cultivation in captivity. The aim of this study was to analyze and describe the main morphological differences in the larval ontogeny of Pseudoplatystoma reticulatum, Leiarius marmoratus, and its hybrid (♀ P. reticulatum × ♂ L. marmoratus), as well as to identify characteristics that can identify the species and their hybrid at the larvae and juvenile stages. 205 L. marmoratus, 210 P. reticulatum, and 205 hybrid specimens were analyzed, all of which were obtained through induced reproduction. Analyses were performed from hatching to 30 days post-hatching. 19 morphometric and 5 meristic characteristics were evaluated, in addition to chromatophore shape and distribution. The specimens were classified into two life periods: Larval (stages: yolk sac, pre-flexion, flexion, and post-flexion) and Juvenile. Newly hatched larvae were transparent, poorly developed, and had a scarcity of chromatophores. During the early stages of larval development, the three groups showed similarities in appearance and proportional dimensions. However, at both the end of the post-flexion stage and at the juvenile period when individuals were approximately 2 cm long, it was possible to differentiate between hybrids and their parental species by their morphometric, meristic, and pigment characteristics. The hybrid, despite occupying an intermediate position in relationship to its parents, exhibited a shape and size more similar to P. reticulatum, its maternal parent.
Keywords: hybrid; larvae; morphology; ontogeny